CONSUMER BEHAVIOUR IN THE METAVERSE: A SYSTEMATIC REVIEW - Balık, Zeynep Sevgi (Tarsus University, 2024)
Consumer behaviour on Metaverse platforms has become an increasingly important topic. This study aims to examine the reasons why consumers purchase virtual products or real products through the Metaverse. For this purpose, Web of Science and Scopus databases were scanned, and 31 articles were examined according to elimination process following the PRISMA 2020 protocol. As a result of the research, it was observed that the most examined variables were value and self-concept. One common finding across the articles is that consumers who view their avatars as extensions of themselves are more likely to purchase items for their avatars.

Metaverse platformlarında tüketici davranışları konusu gittikçe önem kazanan bir konu olmuştur. Tüketicilerin için sanal ürün satın alma ya da Metaverse aracılığı ile gerçek ürünler satın almalarının nedenlerini incelemek amaçlanmıştır. Bu amaçla veri tabanları taranmış ve PRISMA 2020 protokolü izlenerek yapılan eleme sonucunda 31 makale incelenmiştir. Araştırma sonucunda en çok incelenen değişkenlerin değer ve benlik konsepti olduğu gözlemlenmiştir. Avatarlarını kendi uzantıları olarak gören tüketiciler avatarlarına item (nesne) satın alma noktasında daha olumlu eğilim göstermekte ve ayrıca hissedilen telepresence (farklı bir yerde olma hissi) ne kadar iyiyse o derece Metaverse aracılığı ile ürün satın alma eğilimleri de pozitif yönde etkilenmektedir.
Metaverse’de Tüketici Davranışı: Sistematik Bir Derleme
Keywords: Digital Marketing; Dijital Pazarlama